التعسف في استعمال الحق بين الزوجين في قانون الأسرة الجزائري - دونة, حفصية (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2022)
الملخص: تعالج هذه الأطروحة الموسومة ب:"التعسف في استعمال الحق بين الزوجين في قانون الأسرة الجزائري" وفيها تم عرض لما ما جاءت به الشريعة الإسلامية فيما تعلق بموضوع التعسف بين الزوجين وتوضيح موقف قانون الأسرة الجزائري ومناقشته في كل مسألة وعرض مختلف الاجتهادات القضائية التي تخدم موضوع الأطروحة، حيث تعتبر مصدر تفسيري للمواد القانونية، وتسد مختلف الأحكام التي لم ينص عليها قانون الأسرة وتحل الإشكالات القضائية فيها. وتشمل الدراسة كل أشكال التعسف في استعمال الحق سواء من قبل الزوج أو الزوجة وسواء في حالة الزواج أو الطلاق وما يترتب عليهما من آثار وذلك ببيان مفهوم تعسف الزوج في حق زوجته أو العكس ومظاهره وأسبابه والحلول المقترحة لمشكلات تعسف كلا الزوجين. وقد خلص هذا البحث إلى أن الزوج أو الزوجة يكون كل منهما متعسفا في استعمال حقه إذا قصد الإضرار بالطرف الآخر أو استعمل حقه في غير المصلحة التي شرع لها، كما بين مظاهر هذا التعسف في مختلف جوانب الحياة الزوجية ومن أهم العوامل التي تدفع أحد الزوجين إلى التعسف منها عدم الالتزام بالضوابط الشرعية والقانونية وضعف الوازع لديني، والمشاكل الأسرية، والعادات، والتقاليد، والجانب الاقتصادي، وبين أن الإلتزام بالضوابط الشرعية هو الحل السليم لمواجهة هذه الظاهرة. والموضوع مقسم إلى بابين؛ وقد خصص الباب الأول التعسف في استعمال الحق بين الزوجين في الزواج وفيه فصلان الأول التعسف في استعمال الحق في انعقاد الزواج والثاني التعسف في استعمال الحق في تنفيذ الزواج. أما الباب الثاني فقد خصص التعسف في استعمال الحق بين الزوجين في انحلال الزواج وفيه فصلان الأول تعسف الزوج في استعمال حق الطلاق والفصل الثاني تعسف الزوجة في استعمال حق الخلع. وفي الأخير جاءت الخاتمة ملخصة لأهم النتائج والاقتراحات، وألحقت الأطروحة بالمراجع والفهرس. وفي الختام الله أسال أن يكون هذا العمل خالصا لوجهه الكريم فإن أصبت فبتوفيق من الله وحده و إن أخطأت أو قصرت فمن نفسي، والله الموفق والهادي إلى سواء السبيل. Abstract : This thesis deals with the subject entitled : “The abuse of the right between spouses in the Algerian family law.” , what was presented by Islamic law regarding the issue of abuse between spouses, clarification of the position of the Algerian family law and its discussion on every issue and the presentation of the various judicial jurisprudence that serve the topic of the thesis As it is considered an interpretive source for legal articles, it covers various provisions that are not stipulated in the family law and solves judicial problems in it. The study includes all forms of abuse of the right, whether by the husband or wife, whether in the case of marriage or divorce, and their consequences, by showing the concept of the husband’s abuse of his wife’s right or vice versa, its manifestations and causes, and the proposed solutions to the problems of abuse of both spouses. This research concluded that the husband or wife each of them is abusive in the use of his right if he intends to harm the other party or uses his right in a way other than the interest for which it was legislated, as well as the manifestations of this abuse in various aspects of marital life and among the most important factors that push one of the spouses to abuse Including lack of commitment to legal and legal controls, weakness of religious faith, family problems, customs, traditions, and the economic aspect, and that adherence to Sharia controls is the correct solution to confront this phenomenon. The topic is divided into two chapters; The first chapter deals with the abuse of the right between the spouses to marry, and it contains two chapters: the first is the abuse of the right to enter into marriage, and the second is the abuse of the right to implement the marriage. The second chapter deals with abuse of the right between the spouses to dissolve the marriage and it contains two chapters. The first chapter is the abuse of the husband in using the right of divorce, and the second chapter deals with abuse of the wife in using the right of divorce. In the end, the conclusion was a summary of the most important findings and suggestions, and the thesis was attached to the references and the index. In conclusion, I ask God that this work be purely for His honorable sake, and if I am wrong, then with success from God alone, and if I make mistakes or fall short, then it is my soul, and God is the Grantor and the Guide to the straight path.
أطروحة دكتوراه تخصص قانون خاص في الحقوق و العلوم السياسية
Keywords: التعسف، الزوجين، قانون الأسرة الجزائري، استعمال الحق، الضرر، التعويض; abuse, spouses, Algerian family law, use of right, harm, compensation